PELATIHAN PEMBUATAN KUE BERBAHAN DASAR SINGKONG DAN PISANG DI RUMAH PINTAR BSD - Indra, Febryola; Sinaga, Angellita Midian; Fidelia, Eryka; Natalia, Friska Rotua; P. M., Nathan Jouari; Victor, Varrell Isadora (Universitas Pelita Harapan, 2023)
Food is all materials that are processed to be eaten except for drinks and medicines. By seeing an increase in food staples, many people experience difficulties, so a solution to this problem is needed. Banana is a seedless fruit that can grow easily in tropical countries like Indonesia. Bananas have a lot of nutritional content such as calcium, potassium, magnesium, vitamins B, B6 and also vitamin C and can be used as a substitute for staple foods as well as cassava. Cassava is the tuber of the cassava plant which is located on a root that contains carbohydrates. In this PKM, the writing team uses bananas and cassava as the main ingredients for processed foods that will be studied by the participants, namely Cassava Cake and Banoffee.abstract in bahasaMakanan merupakan semua bahan yang diolah untuk dimakan kecuali minuman dan obat-obatan. Dengan melihat adanya kenaikan bahan pokok makanan membuat banyak masyarakat kesulitan sehingga dibutuhkannya solusi permasalahan tersebut. Pisang merupakan buah tanpa biji yang dapat tumbuh dengan mudah di negara beriklim tropis seperti Indonesia. Pisang memiliki banyak kandungan gizi seperti kalsium, kalium, magnesium, vitamin B, B6 dan juga vitamin C dan dapat digunakan sebagai bahan pengganti makanan pokok begitu juga singkong. Singkong merupakan umbi dari tanaman singkong yang terletak pada akar yang memiliki kandungan karbohidrat. Pada PKM ini tim penulis menggunakan pisang dan juga singkong sebagai bahan utama olahan makanan yang akan dipelajari oleh peserta yaitu Cassava Cake dan Banoffee.